Enhanced antibacterial activity of Ocimum sanctum leaf extract mediated hydroxyapatite and hydroxyapatite-iron oxide nanocomposites - M. Rokonozzaman; Kishan Nandi Shoudho; N. Banik; Mehedi Hasan Pritom; M. Ariful Haque; M.K. Alam; N. Begum; Shoeb Ahmed; I.A. Khan; A.S.M. Al Amin; M.N.I. Khan (Current Research in Green and Sustainable Chemistry)
Hydroxyapatite (HA) is frequently used in a variety of biomedical applications especially in orthopedics and dental because of its outstanding bioactivity and biocompatibility. On the other hand, HA lacks inherent antibacterial properties, shows poor mechanical strength, and infection issues are still one of the main causes of implant failure. Consequently, antibacterial HA may be a potential material for HA applications. For any potential uses of modified hydroxyapatite, such as in medicine or environmental protection, magnetite (Fe3O4) may be a crucial element because it has good mechanical properties and is preferred in biomedical systems. Moreover, Fe3O4 is biocompatible and basically nontoxic to humans. Therefore, the present study aims to find a novel approach that may improve the antibacterial activity of HA and HA-Fe3O4 nanocomposites and provide low toxicity to humans. The synthesized HA and HA -Fe3O4 nanocomposites were characterized by XRD, FTIR, SEM, EDX, and Zeta potential analyzer. Moreover, antibacterial activity tests confirmed that the utilization of Ocimum sanctum leaf extract as a reaction medium in HA and HA-Fe3O4 nanocomposites synthesis improved antibacterial activity against Escherichia coli and Staphylococcus aureus. This research demonstrates the green synthesis of HA and HA-Fe3O4 nanocomposites using Ocimum sanctum leaf extract by hydrothermal method, opening the door for potential applications in biomedical fields.